PENERAPAN METODE ALGORITMA C4.5 DAN NAIVE BAYES UNTUK PREDIKSI PENYAKIT JANTUNG - Sihotang, Putri Anasia; Sitanggang, Delima (Politeknik Bisnis Indonesia, 2024)
This study aims to compare the C4.5 Decision Tree and Naive Bayes algorithms in predicting heart disease to determine the most efficient algorithm. Heart disease is one of the leading causes of global mortality, including in Indonesia, due to vascular damage that disrupts the optimal functioning of the heart. The dataset used comes from the UCI Machine Learning Repository and the Kaggle website's